Modeling rolling contact fatigue lives of composite materials based on the dual beam FIB/SEM technique. (February 2016) - Zhou, Qinghua; Xie, Lechun; Wang, Xueli; Jin, Xiaoqing; Wang, Zhanjiang; Wang, Jiaxu; Jia, Zhihong; Keer, Leon M.; Wang, Qian
Highlights: Microstructure reconstruction of composites based on the FIB/SEM technique. Development of a new numerical RCF life modeling method. Correlation of RCF life with inhomogeneous reinforcement volume fraction. Abstract: Rolling contact experiments of (TiB + TiC)/Ti–6Al–4V composites reveal that inhomogeneous reinforcements reduce the materials' rolling-contact fatigue (RCF) lives. The composite microstructures are examined and reconstructed based on the dual-beam focus ion beam scanning electron microscopy (FIB/SEM) technique. Integration of the microstructure-based stress analysis approach and Zaretsky's RCF life prediction methodology leads to a new numerical RCF life modeling method. The newly developed mesh differential refinement scheme, together with the fast Fourier Transform techniques, is utilized to improve the efficiency and versatility of the proposed method. The RCF lives of the composites predicted by the new model are then compared with the experimental data, illustrating the effectiveness of the proposed method.